An asymmetric synthesis of (+)-Scrodentoid A from dehydroabietic acid. (9th April 2021) - Song, Yi-Kang; Liu, Li; Wang, Jun-Jie; Qian, Fei; Yang, Mao-Qi; Zhang, Liu-Qiang; Fu, Jian-Guo; Li, Yi-Ming; Feng, Chen-Guo
Abstract: An efficient synthesis of (+)-scrodentoid A was accomplished starting from commercially available dehydroabietic acid. Key reactions in the synthesis include oxidative decarboxylation of dehydroabietic acid and C–H bond oxidation on arene. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Leave this area blank for abstract info. Image 1